2008
DOI: 10.1523/jneurosci.0504-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2 Is Activated by Cannabidiol and Mediates CGRP Release in Cultured Rat Dorsal Root Ganglion Neurons

Abstract: Transient receptor potential V2 (TRPV2) has been proposed to be a high-threshold thermosensor. However, further elucidation of the channel properties and physiological role of TRPV2 have been hindered by the lack of selective pharmacological tools as well as by the species-dependent differences in the activation of this channel. In the present study, we have used cell-based calcium mobilization and electrophysiological assays to identify and characterize several novel cannabinoid TRPV2 agonists. Among these, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
294
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 341 publications
(306 citation statements)
references
References 35 publications
8
294
1
3
Order By: Relevance
“…In contrast to the above studies, comparable fluorescencebased Ca 2+ imaging in HEK293 cells expressing rat TRPV1 receptors revealed that CBD (100 μM) produced a response that was only 21% of that produced by the positive control, capsaicin (500 nM), which was insufficient to determine reliably an EC 50 value [96]. Furthermore, a recent study used patch clamp techniques to assess the effect of CBD (3-30 μM) on the bidirectional current recorded in HEK293 cells overexpressing rat TRPV1 receptors that can be evoked by application of the TRPV1 agonist, capsaicin (1-10 μM) [98].…”
Section: Trp Channelsmentioning
confidence: 56%
See 3 more Smart Citations
“…In contrast to the above studies, comparable fluorescencebased Ca 2+ imaging in HEK293 cells expressing rat TRPV1 receptors revealed that CBD (100 μM) produced a response that was only 21% of that produced by the positive control, capsaicin (500 nM), which was insufficient to determine reliably an EC 50 value [96]. Furthermore, a recent study used patch clamp techniques to assess the effect of CBD (3-30 μM) on the bidirectional current recorded in HEK293 cells overexpressing rat TRPV1 receptors that can be evoked by application of the TRPV1 agonist, capsaicin (1-10 μM) [98].…”
Section: Trp Channelsmentioning
confidence: 56%
“…In addition to reports of TRPV1 receptor agonism, CBD has also been reported to interact with the TRPV2 receptor. In the first study reporting such effects [96], CBD agonized human TRPV2 receptors overexpressed in HEK293 cells when assessed using a fluorescence-based assay, a finding subsequently confirmed using patch clamp electrophysiology and extended to reveal similar effects upon rat TRPV2 overexpressed in the same cell line, although with markedly different potency [EC 50 = 3.7 μM (human) vs 31.7 μM (rat)] (Table 3). CBD effects upon rat TRPV2 receptors were also separately investigated in the same expression system and using patch clamp electrophysiology [98].…”
Section: Trp Channelsmentioning
confidence: 82%
See 2 more Smart Citations
“…TRPV1 ion channels have important functions as cellular sensors, and are involved in nociception, taste perception, thermosensation, mechano‐ and osmolarity sensing, and regulation of signal transmission 15, 55, 56. In addition to ECS and physicochemical activators,15, 33, 55, 56, 57, 58 TRPV1 is activated by tetrahydrocannabinol, cannabinol, cannabigerol and some propyl homologs of THC and cannabigerol 59, 60, 61, 62, 63, 64, 65, 66, 67. Cannabichromene (CBC), cannabidiol, and cannabinol are strong TRPA1 agonists and desensitizers, and THCV (from a botanical extract) is a potent regulator of TRPA1 62…”
Section: The Endocannabinoid Systemmentioning
confidence: 99%